Event concept of EMPATHY in English juvenile fantasy prose - Ivanotchak, Nataliia; Doichyk, Oksana (Cognition, Communication, Discourse, 2020)
The article deals with the research of lingual cognitive and pragmatic aspects of empathy in juvenile fantasy prose. It reveals the nature of empathy from the perspective of cognitive linguistics, linguistic emotiology, and pragmalinguistics. The properties of empathy verbalization in juvenile fantasy prose are researched, namely the lexical and grammatical means of verbalization of the corresponding concepts and empathic illocutionary types of psychological support in discursive contexts of the English juvenile fantasy prose. The implementation of both pragmatic and lingual cognitive research findings in the light of cognitive-discursive paradigm revealed the basis of empathy conceptualization and the multifaceted empathic context. The interpretation of empathy meaning is performed by means of schematic cognitive mapping, as well as via establishing the correlation of empathy determinants in discursive contexts which present the communicative strategy of empathy. The componential analysis of definitions of various affective and cognitive states and processes connected with empathy, such as compassion, understanding, sympathy etc., as well as their antonyms, and determination of weight, status and hierarchy of the corresponding semes in vocabulary definitions, showed that generally accepted and empirically proved division of empathy into affective and cognitive is reflected in the language. The analyses revealed affective (feeling, sympathy, sorrow) cognitive (knowledge, ability, understanding) semes in the definitions of empathy types attributing them to either affective or cognitive group. Types of empathy, which belong to the same affective or cognitive group, are not equal in the degree of empathy manifestation. The factor or driving force for upgrading (or downgrading) to a different level is action. While partly addressing social functioning, empathy is turned to cognition and emotion, thus being framed as a social psychological event concept. As an event concept empathy emerges in consciousness and in verbal behavior under the influence of human activity in a certain communicative-pragmatic situation, arising in a variety of constituents of the cognitive and affective parcels of the domain of empathy and unfolding in two scripts which reflect its active and passive manifestations.